2010
DOI: 10.1007/s00586-010-1555-y
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular changes after PMMA vertebroplasty in sheep: the effect of bone marrow removal using pulsed jet-lavage

Abstract: Clinically, the displacement of intravertebral fat into the circulation during vertebroplasty is reported to lead to problems in elderly patients and can represent a serious complication, especially when multiple levels have to be treated. An in vitro study has shown the feasibility of removing intravertebral fat by pulsed jet-lavage prior to vertebroplasty, potentially reducing the embolization of bone marrow fat from the vertebral bodies and alleviating the cardiovascular changes elicited by pulmonary fat em… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
31
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 19 publications
2
31
0
Order By: Relevance
“…It could be shown that (jet)-lavage does not cause cardiovascular reaction in combination with contralateral application of vacuum and can significantly decrease the embolic load in sheep [30]. Similar results, significant reductions of cement leakage, were found by Mohamed et al [33], using an unipedicular aspiration technique (without lavage) in a vertebroplasty model.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…It could be shown that (jet)-lavage does not cause cardiovascular reaction in combination with contralateral application of vacuum and can significantly decrease the embolic load in sheep [30]. Similar results, significant reductions of cement leakage, were found by Mohamed et al [33], using an unipedicular aspiration technique (without lavage) in a vertebroplasty model.…”
Section: Discussionsupporting
confidence: 80%
“…This lowers potentially the risk of cement leakage and fat embolization and makes vertebral augmentation safer [29]. It could be shown in a sheep model that lavage of the bone marrow prior to VP prevents cardiovascular complications, reduces injection forces and allows a better control of cement distribution pattern with less leakage [30,31]. The advantages of lavage technique were not yet assessed in clinical studies.…”
Section: Introductionmentioning
confidence: 97%
“…To prevent pulmonary symptoms, the number of augmented vertebrae during prophylactic multi-segmental VP should be limited to six levels per session or 25-30 cc of PMMA [36]. In a sheep model, it could be shown that lavage of the bone marrow prior to VP prevents cardiovascular complications, reduces injection pressures and allows a better control of cement distribution, with less leakage [37,38].…”
Section: Complicationsmentioning
confidence: 99%
“…[7][8][9] As long term results are highly required it is mandatory to develop new technologies or to improve the existing ones, as they exhibit several disadvantages. [10][11][12][13][14][15][16][17] Poly(methyl methacrylate) (PMMA) and its derivatives have been successfully used in orthopedic surgeries as bone filler in vertebroplasty. 18 19 Also, PMMA is the most common and successful adhesive used to anchor orthopedic implants to bone, as evidenced by data from longterm national joint registries.…”
Section: Introductionmentioning
confidence: 99%